Espaço e tempo nas Minas do Camaquã em Caçapava do Sul/RS - Silva, Rogério Marques (2008)
Currently, one lives a reality where the economic issue has great importance. Facing this, the geographical space, a product of socio-economic changes over time, can serve as an important focus of research in what refer to such trends. In this context, it is found Minas do Camaquã, at the municipality of Caçapava do Sul, in Rio Grande do Sul, an assembly of working towns formed over 130 years of copper exploitation, as object of study, which purpose is to attempt to understand the spatial changes throughout the process of copper extraction and the future trends for this space. The methodology of the research starts up from a dialectic vision, where in the beginning was researched the history of the site survey in order to study the different special conformations along the copper production. Later, we tried to understand the dynamics of space during and after the activity of mining through interviews and skilled application of questionnaires, verifying as well the probable trends space for the coming years. From 1942, the Brazilian Copper Company - CBC came to extract copper in the region. From this moment on, the local landscape would include a structure formed by an urban industrial area and a set of seven towns in addition to clubs, squares, hospitals and others. After 50 years, the depth of copper reserves combined with low prices and Brazilian policy of privatization, were the reasons that prompted the closing activities in 1996. From this moment on, all the mining structure was abandoned. From about 5000 residents, remained around 400. Whole towns have been shut down. Buildings were demolished. After 12 years form the closing of activities, one can verify that there are some ideas being worked on, but still far from solve the needs of the city. Successive municipal governments and their neglect with the local make today from Minas do Camaquã, a post-industrial space which peculiarities keep resemblance to many degraded areas, like railway cities shut deactivated and former military bases, in what refer to the underprivileged position within the production process. The mining return face of the current studies of the geology of the region and tourist activity because of the beautiful scenery of this region, come as opportunities to develop the local economy.